MUGA scan of apicoaortic conduit with incidental finding of pseudoaneurysm and repeat scan after aneurysmectomy - Won Park; Kevin Tsai; Kishore Nallu; In Seo (World Journal of Nuclear Medicine)
This is a case of a 77-year-old woman who underwent a multiple-gated acquisition (MUGA) scan to evaluate her cardiac function after initially presenting with chest pain and shortness of breath. The scan revealed the presence of an apicoaortic conduit (AAC) and incidentally found a left ventricular pseudoaneurysm. After aneurysmectomy, the MUGA scan was repeated.